12-3n=-36-6n

Simple and best practice solution for 12-3n=-36-6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-3n=-36-6n equation:


Simplifying
12 + -3n = -36 + -6n

Solving
12 + -3n = -36 + -6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6n' to each side of the equation.
12 + -3n + 6n = -36 + -6n + 6n

Combine like terms: -3n + 6n = 3n
12 + 3n = -36 + -6n + 6n

Combine like terms: -6n + 6n = 0
12 + 3n = -36 + 0
12 + 3n = -36

Add '-12' to each side of the equation.
12 + -12 + 3n = -36 + -12

Combine like terms: 12 + -12 = 0
0 + 3n = -36 + -12
3n = -36 + -12

Combine like terms: -36 + -12 = -48
3n = -48

Divide each side by '3'.
n = -16

Simplifying
n = -16

See similar equations:

| 12-2(t-3)=-8t | | 5y-12= | | -25y+18=-15y-25 | | x^2+16-28=0 | | 5x-0.8=-0.2+3x | | 4x+4=9x | | (7x+5)(3x-8)= | | x+[x+1]=1.10 | | y=-5+2(-2) | | a^2+10ab+25b^2-49=0 | | (x+49)(x+4)=O | | x^2-5x+6.25-14=6.25 | | 1x-2y=10 | | w+9=-7 | | 5-4x=x-1.5 | | 5x-0.8=0.2+3x | | 6y-1y-12= | | =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 |

Equations solver categories